Handbook of Hospitality Human Resources Management - Tesone (ButterworthHeinemann, 2012)
This is an authoritative resource comprising an edited collection of papers, which review and discuss this crucial aspect of hospitality, whilst illustrating how theories and concepts can be applied to the hospitality industry.